Vinasse-Based Slow-Release Organo-Mineral Fertilizer with Chitosan-Bentonite Matrix - Qudus, Nur; Kusumaningtyas, Ratna Dewi; Syamrizal, Zakky; Zakaria, Zainul Akmar; Hartanto, Dhoni (Universitas Negeri Semarang, 2021)
Controlling the release rate of the nitrogen-phosphorus-potassium (NPK) for the soil fertilized can enhance the fertilizer efficiency and reduce the drawback for the environmental. In this work, a novel slow-release organo-mineral fertilizer was produced from the vinasse, which was blended with the NPK and the chitosan-bentonite matrix. The NPK used as additional nutrients source and the chitosan-bentonite matrix was performed as a barrier to prevent the nitrogen, phosphorus, and potassium from a rapid dissolving. The NPK release rate was measured and analyzed after 3, 6, 9, and 12 days using the incubation method and leaching test. The most efficient release rate was obtained when a dry vinasse mixed with 9% NPK and 5% chitosan-bentonite matrix with the ratio of 8:2. The vinasse-based slow-release of organo-mineral fertilizer (SR-OMF) was compared to the vinasse organo-mineral fertilizer (OMF). The result indicated that the NPK release rate in the vinasse-based SR-OMF was lower compared to that in the vinasse OMF.